1997
DOI: 10.1159/000190198
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of a Newly Developed Antioxidative Agent (OPC-15161) on Experimental Immune Complex Nephritis

Abstract: The effect of a newly developed free radical scavenger (OPC-15161) on the progression of nephrotoxic serum (NTS) nephritis was evaluated. NTS nephritis rats were sacrificed immediately before and 1, 2, 3, 6, and 24 h and 13 and 19 days after intravenous injection of NTS. The tissue content of phosphatidylcholine hydroperoxide, the activity of superoxide, the activity of superoxide dismutase in the renal cortex, and the serum malondialdehyde levels were measured. The phosphatidylcholine hydroperoxide content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Minimal-change disease, membranous glomerulonephritis, neutrophil-induced damage, ischemic or toxic acute renal failure, obstructive nephropathy, and progressive renal failure are kidney diseases where ROS play a role in pathogenesis (10,12). In addition, cobra venom factor (25), daunomycin-induced nephropathy (20), immune complex nephritis (29), Masugi nephritis (38), and adriamycin nephropathy (19) are some examples for oxidative stress inducedproteinuria found in experimental kidney disease models. Antioxidant interventions could be effective in reducing proteinuria with superoxide dismutase (19), dimethyl thiourea (20), catalase (35), probucol (17), and vitamins C and E (15) being utilized in such processes.…”
Section: Discussionmentioning
confidence: 99%
“…Minimal-change disease, membranous glomerulonephritis, neutrophil-induced damage, ischemic or toxic acute renal failure, obstructive nephropathy, and progressive renal failure are kidney diseases where ROS play a role in pathogenesis (10,12). In addition, cobra venom factor (25), daunomycin-induced nephropathy (20), immune complex nephritis (29), Masugi nephritis (38), and adriamycin nephropathy (19) are some examples for oxidative stress inducedproteinuria found in experimental kidney disease models. Antioxidant interventions could be effective in reducing proteinuria with superoxide dismutase (19), dimethyl thiourea (20), catalase (35), probucol (17), and vitamins C and E (15) being utilized in such processes.…”
Section: Discussionmentioning
confidence: 99%
“…Puromycin aminonucleoside-induced nephritis [31], immune complex nephritis [32], Masugi nephritis [33], adriamycin nephropathy [34] and anti-glomerular basement membrane antibody glomerulonephritis [35] are some examples for oxidant stress-induced proteinuria occurred in experimental kidney disease models. H 2 O 2 administration into the renal artery [36] and antioxidant vitamin deficiency [37] are other two situations in which proteinuria exist.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the plasma pentosidine level in patients with mild renal dysfunction (creatinine clearance 71–90 ml/min) was 1.8-fold higher than that in normal subjects (p < 0.01), while creatinine and urea-nitrogen levels were not significantly elevated in this group of patients. Although Daimon et al [17]and Sanaka et al [18]reported that the plasma pentosidine level rose with a decrease in the kidney function, such a conclusion was obtained by comparing plasma pentosidine levels of patients undergoing HD or peritoneal dialysis with those of healthy people. In contrast to their study, we compared the pentosidine levels according to the creatinine clearance in patients with CRF in the conservative stage.…”
Section: Discussionmentioning
confidence: 99%
“…Because the oxidation reaction is a requirement of pentosidine production, pentosidine has been recently regarded as a glycoxidation product, and it is attracting attention as a possible marker that reflects oxidation and glycosylation of protein in vivo [17, 18, 19, 20, 21, 22, 23]. In CRF patients, the activity of peroxidase associated with the scavenging system (human plasma glutathione peroxidase) of oxygen radicals and the concentration of selenium, the composing element, is markedly lower as compared with healthy subjects [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation